PHONOLOGICAL APPROACH TO THE ANDIJAN DIALECT - Satimboyeva Onorkhon Anvarjon qizi (Scholar Express Journal, 2025)
This article presents the views of linguists on the Andijan dialect of the Uzbek language. In addition, the phonological features of this dialect are studied based on a phonological approach
Keywords: Vowel; long vowel; consonant